2023
DOI: 10.3390/ijms24032256
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering of Soybean Oil and Its Impact on Agronomic Traits

Abstract: Soybean is a major oil crop and is also a dominant source of nutritional protein. The 20% seed oil content (SOC) of soybean is much lower than that in most oil crops and the fatty acid composition of its native oil cannot meet the specifications for some applications in the food and industrial sectors. Considerable effort has been expended on soybean bioengineering to tailor fatty acid profiles and improve SOC. Although significant advancements have been made, such as the creation of high-oleic acid soybean oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Compared with the other three copies, it was found that BnaSAD2.A3 plays a more important role in C18:0‐ACP desaturation in seeds (Huang et al., 2023). Five SAD s have been characterized in the soybean genome, with different expression patterns (Song et al., 2023). Functional analysis of mutants using tilling by sequencing showed that mutations in GmSACCPD‐A , GmSACCPD‐B , and GmSACCPD‐D resulted in a significant ( P < 0.01) increases in stearic acid content, with average values of 6.75%, 6.61%, and 6.03% (Lakhssassi et al., 2020).…”
Section: Key Genes Contributing To Fa and Tag Biosynthesis In Major O...mentioning
confidence: 99%
“…Compared with the other three copies, it was found that BnaSAD2.A3 plays a more important role in C18:0‐ACP desaturation in seeds (Huang et al., 2023). Five SAD s have been characterized in the soybean genome, with different expression patterns (Song et al., 2023). Functional analysis of mutants using tilling by sequencing showed that mutations in GmSACCPD‐A , GmSACCPD‐B , and GmSACCPD‐D resulted in a significant ( P < 0.01) increases in stearic acid content, with average values of 6.75%, 6.61%, and 6.03% (Lakhssassi et al., 2020).…”
Section: Key Genes Contributing To Fa and Tag Biosynthesis In Major O...mentioning
confidence: 99%
“…Soybean ( Glycine max ), a herbaceous annual plant in the family Fabaceae, is among the most important crops in the world, playing irreplaceable roles in providing humans and livestock with high-quality proteins and balanced fatty acids [ 1 , 2 , 3 , 4 , 5 ]. Phytonutrients such as saponins, vitamins, and flavonoids in soybean also contribute special health nutrition and pharmacological effects to humans [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11,21] The WCO, as most triglycerides, is comprised by fatty saturated and unsaturated chains linked by ester carbonyls groups and glycerol, with varying amounts of free fatty acids (produced by the frying process). [22,23] Due to its composition, WCO can be effortless modi ed to obtain lubricants, greases, para ns, soaps, resins, biodiesel and others. [11,24] Another residual oil with similar applications can be obtained by extraction from silkworm pupae (Bombyx mori), an agroindustrial residue from silk processing, to obtain extracted protein rich materials proper for animal feed.…”
mentioning
confidence: 99%